DIFFERENCES IN THE REPETITIVE POWER BETWEEN SPORTSMEN AND NON- SPORTSMEN OF THE 3RD YEAR OF HIGH SCHOOL STUDENTS - Jasmin Muminović; Nenad Trninić; Uroš Milinković (Sport Scientific And Practical Aspects, 2025)
The subject of the research is to determine the current state of repetitive power in high school children engaged in sports and those who do not train any sport. The repetitive power of 3rd grade high school students was researched. The study was conducted on a sample of 60 respondents. Three tests were used to test the repetitive power. Repetitive power was measured by trunk lifting in 30s i.e. abs (ABS), push-ups in 30s (PUP), as well as squats within 30s (SQT). The results of motor skills tests have shown that high school students who are engaged in sports are more prepared and achieve greater results than those who do not do any sports